Cold-start NOx emissions: Diesel and waste lubricating oil as a fuel additive. (15th February 2021) - Zare, Ali; Bodisco, Timothy A.; Jafari, Mohammad; Verma, Puneet; Yang, Liping; Babaie, Meisam; Rahman, M.M; Banks, Andrew; Ristovski, Zoran D.; Brown, Richard J.; Stevanovic, Svetlana
Highlights: Diesel was blended with 1% and 5% waste lubricating oil. During cold start, NOx emissions were higher than hot start. During cold start, NOx increased as the engine warmed up. NOx emissions had a direct correlation with maximum rate of pressure rise. NOx emissions had an inverse correlation with maximum in-cylinder pressure. Abstract: NOx emissions from diesel engines are a concern from both environmental and health perspectives. Recently this attention has targeted cold-start emissions highlighting that emission after-treatment systems are not effective in this period. Using a 6-cylinder, turbocharged, common-rail diesel engine, the current research investigates NOx emissions during cold-start using different engine performance parameters. In addition, it studies the influence of waste lubricating oil on NOx emissions introducing it as a fuel additive (1 and 5% by volume). To interpret the NOx formation, this study evaluates different parameters: exhaust gas temperature, engine oil temperature, engine coolant temperature, start of injection/combustion, in-cylinder pressure, heat release rate, maximum in-cylinder pressure and maximum rate of pressure rise. This study clarified how cold-start NOx increases as the engine is warming up while in general cold-start NOx is higher than hot-start. Results showed that in comparison with warmed up condition, during cold-start NOx, maximum in-cylinder pressure and maximum rate of pressure rise were higher; while start of injection, start of combustion and ignition delay were lower. During cold-start increased engine temperature was associated with decreasing maximum rate of pressure rise and peak apparent heat release rate. During cold-start NOx increased with temperature and it dropped sharply due to the delayed start of injection. This study also showed that using waste lubricating oil decreased NOx and maximum rate of pressure rise; and increased maximum in-cylinder pressure. NOx had a direct correlation with the maximum rate of pressure rise; and an inverse correlation with the maximum in-cylinder pressure.